SNAP: Working to Improve Nutrition and Health - Mosley, Mary (MD Conference Express, 2014)
The Supplemental Nutrition Assistance Program (SNAP) provides federal funds to low-income persons to purchase food to address food insecurity and improve nutrition and health. SNAP has had a substantial antipoverty impact, improved metabolic outcomes, and improved dietary intake and health status, as discussed in this article.